Formulation and Evaluation of Gel Containing Fluconazole Microsponges - Syed, Shoaeb Mohammad; Gaikwad, Satyapal S; Wagh, Sachin (Asian Journal of Pharmaceutical Research and Development, 2020)
The aim of current study was to develop gel containing Fluconazole microsponges; the microsponges were prepared by quasi emulsion solvent diffusion method using eudragit RL100 the gel was prepared and evaluated for various parameters and Invitro release studies. All the factors studied had an influence on the physical characteristics of the microsponges. In vitro dissolution results showed that the release rate of Fluconazole was modified in all formulations. The Fluconazole-loaded Eudragit RL 100 microspheres showed a good release characteristic and were stable under the condition studied.